General Ordinances of the City of Aspen, § 152, in Aspen Daily Times, Jul. 27, 1886, at 3-6 - (:unkn) unknown (My University, 1886)
§If any person shall, within this city, fire or discharge any cannon, gun, fowling piece,, pistol, or fire-arms of any description, or fire, explode or set off any squib, cracker or other thing containing powder or other combustible or explosive material, without permission from the mayor (which permission shall limit the time of such firing, and shall be subject to be revoked by the mayor or city council at any time after the same has been granted), every such person shall, on conviction, be fined in a sum not less than one dollar nor more than one hundred dollars.
Keywords: DISCHARGE